2016
DOI: 10.3892/ol.2016.4650
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-5 localisation in human endometrial cancer shifts from epithelial to stromal with increasing tumour grade, and silencing promotes endometrial epithelial cancer cell proliferation

Abstract: Abstract. Endometrial cancer is the most common invasive gynaecological malignancy. While endocrine, genetic and inflammatory factors are thought to contribute to its pathogenesis, its precise etiology and molecular regulators remain poorly understood. Fibulin-5 is an extracellular matrix (ECM) protein that inhibits cell growth and invasion in several cancer cell types and is downregulated in a number of types of human cancer. However, it is unknown whether fibulin-5 plays a role in endometrial tumourigenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…The comprehensive molecular characteristic of the endometrial cancer cell lines faithfully replicate the histological and morphological features of type I and II endometrial cancer. Furthermore, these two types of endometrial cancer represented by Ishikawa, HEC-1-A, HEC-1-B and KLE cell lines show a strong differences in motility and proliferation rate that was observed in our study and is in agreement with other researchers’ results (Bansal et al 2009 ; Goto et al 2008 ; Lu et al 2015 ; Winship et al 2016 ). Modulation of gene expression pattern, cellular signaling pathways changes and receptors activity induced by plethora of therapeutics tested in multiple studies, disclosed various morphological changes in endometrial cancer cells structure, as well alterations in proliferation rate, survival, migration and invasion (Bansal et al 2009 ; Diaz-Valdivia et al 2015 ; Lelle et al 1993 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The comprehensive molecular characteristic of the endometrial cancer cell lines faithfully replicate the histological and morphological features of type I and II endometrial cancer. Furthermore, these two types of endometrial cancer represented by Ishikawa, HEC-1-A, HEC-1-B and KLE cell lines show a strong differences in motility and proliferation rate that was observed in our study and is in agreement with other researchers’ results (Bansal et al 2009 ; Goto et al 2008 ; Lu et al 2015 ; Winship et al 2016 ). Modulation of gene expression pattern, cellular signaling pathways changes and receptors activity induced by plethora of therapeutics tested in multiple studies, disclosed various morphological changes in endometrial cancer cells structure, as well alterations in proliferation rate, survival, migration and invasion (Bansal et al 2009 ; Diaz-Valdivia et al 2015 ; Lelle et al 1993 ).…”
Section: Discussionsupporting
confidence: 93%
“…Schaefer et al ( 2010 ) used similar cell concentration to determine the cytotoxic effect of cadmium chloride on Ishikawa cells by real-time xCELLigence cell impedance analysis. The cell plating concentration, time for cell attachment and spreading as well as compound incubation time presented by Winship et al ( 2016 ), also supported our observation about Ishikawa cells growth characteristic. The optimum seeding concentration for KLE cell line in our experiment was established in range of 40,000–20,000 cells/well.…”
Section: Discussionsupporting
confidence: 91%
“…Fibulin-5 mRNA expression is downregulated in the majority of human tumors, particularly in metastatic malignancies of the kidney, breast, ovary, and colon, suggesting its inhibitory role in advanced cancer development [ 118 ]. A recent study showed that fibulin-5 is downregulated in human endometrial cancer and that fibulin-5 knockdown in endometrial epithelial cancer cells enhances adhesion and proliferation of cancer cells, indicating its antitumorigenic role in women [ 121 ]. On the contrary, fibulin-5 was shown to enhance the malignancy of human fibrosarcoma cells [ 118 ] and mammary epithelial cells via promoting EMT [ 122 ].…”
Section: Fibulin Familymentioning
confidence: 99%
“…Overexpression of fibulin-5 enhances basal and TGF-β-stimulated activation of ERK1/2 and p38MAPK in 3T3-L1 fibroblasts [ 118 ]. Fibulin-5 expression is enhanced by TGF-β in human endometrial epithelial cancer cells [ 121 ]. In pancreatic ductal adenocarcinoma, fibulin-5 is produced by stromal cells, and its expression is induced by TGF-β via PI3K/AKT signaling pathway [ 146 ], serving as a protumorigenic factor.…”
Section: Interaction Between Fibulins and Tgf-βmentioning
confidence: 99%
See 1 more Smart Citation